1957
DOI: 10.1017/s0022172400037189
|View full text |Cite
|
Sign up to set email alerts
|

The use of influenza virus labelled with radio-sulpher in studies of the early stages of the interaction of virus with the host cell

Abstract: 1. Influenza virus can be labelled with 35S by cultivation in fertile eggs into which radioactive methionine has been introduced.2. When virus labelled with 35S is fractionated by ether treatment the nucleoprotein soluble antigen fraction contains 15 % of the 35S, the haemagglutinin also contains 15%, while the denatured envelope protein contains 70% of the 35S.3. When sulphur-labelled virus is introduced as a primary inoculum in fertile eggs and extracts of the chorioallantoic membrane are made 1–20 % of 35S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1959
1959
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The concept of Fazekas de St. Groth (17) that attached virus is engulfed or pinocytosed by the host cell (viropexis), although accepted (18,19) in explanation of virus penetration, must be reconsidered in the light of recent findings (20,21). Little is known of the stages immediately following poliovirus attachment to cells, except that most of the attached virus enters an eclipse period (4,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of Fazekas de St. Groth (17) that attached virus is engulfed or pinocytosed by the host cell (viropexis), although accepted (18,19) in explanation of virus penetration, must be reconsidered in the light of recent findings (20,21). Little is known of the stages immediately following poliovirus attachment to cells, except that most of the attached virus enters an eclipse period (4,22).…”
Section: Discussionmentioning
confidence: 99%
“…If so, since externally applied ribonuclease was harmless during penetration, it must be assumed that the protein coat releases its RNA content into or through the cell membrane without exposing it to external fluid. It is interesting that Hoyle and Finter (21) have reported that influenza virus infection is initiated when viral nucleoprotein enters the cell, leaving protein envelope and hemagglutinin on the cell surface. These findings suggest a similarity in the role of nucleic acid in penetration by mammalian and bacterial viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Three i m m a t u r e particles, one of which is partly obscured by a silver grain. Au (30), M, X 85,000.…”
Section: Figure 32mentioning
confidence: 99%
“…Accordingly, the site of release of viral nucleic acid is unknown and its subsequent fate cannot be followed easily. To obviate the difficulty of distinguishing virus and host cell material, animal viruses have been tagged by radioisotopes and the fate of the labeled material ascertained chemically during the virus-host cell interaction (30,46). As a result of such experiments with myxoviruses, it was suggested that initial release of the infecting component of influenza virus may occur at the cell surface (30).…”
Section: Introductionmentioning
confidence: 99%
“…Dissenting opinions, however, have been voiced. Hoyle and Finter (16) [see also Wecker and Schafer (32)] concluded from an investigation of influenza virus labeled with radioactive sulfur "that on entry into the cell the virus nucleoprotein is hydrolyzed with release of amino-acid and free nucleic acid, while the virus envelope protein and haemagglutinin remain on the cell surface." Subsequently, Zhdanov et al (35) reached a similar conclusion based on autoradiographic studies of Sendai virus.…”
mentioning
confidence: 99%